Finite Convergence of the Partial Inverse Algorithm - Daldoul, M. (Journal of optimization theory and applications, 1997)
In Refs. 1-2, Lefebvre and Michelot proved the finite convergence of the partial inverse algorithm applied to a polyhedral convex function by means of some suitable tools of convex analysis. They obtained their result under some assumptions on the primal and dual solution sets. The aim of this note is to show that the proof can be extended to remove the nasty assumption on the dual solution set. The result is in conformity with the proof given in Ref. 3, which has been obtained using the concept of folding.